Approaches in teaching foods and nutrition in the high school - Balinsat, Mary M. (1968)
The study analyzed the different approaches in teaching food and nutrition in high school with the hope that these will provide a more meaningful learning experience for the students and will bring about a better understanding and retention of the concepts learned.
Thesis (M.A.T. Home Economics)--University of the Philippines
Keywords: Nutrition -- Study and teaching